PREVALENCE, ANTIMICROBIAL RESISTANCE, AND RISK FACTORS OF ESBL-PRODUCING ENTEROBACTERIACEAE IN PATIENTS WITH URINARY TRACT INFECTIONS (Journal of Medical & Health Sciences Review, 2025)
Urinary tract infections (UTIs) are among the most common bacterial infections, frequently caused by Enterobacteriaceae. The emergence of extended-spectrum beta-lactamase (ESBL)-producing strains poses a significant challenge due to multidrug resistance, complicating empiric therapy. This study aimed to determine the prevalence of ESBL-producing Enterobacteriaceae, their antimicrobial susceptibility patterns, and associated risk factors in patients with suspected UTIs. A total of 200 urine samples were collected from patients with suspected UTIs. Bacterial isolates were identified, and antimicrobial susceptibility testing was performed. ESBL production was confirmed using standard phenotypic methods. Patient demographics, clinical characteristics, and risk factors were recorded. Data were analyzed to evaluate the prevalence, species distribution, resistance patterns, and associated risk factors for ESBL-producing isolates. Of 200 samples, 150 (75%) showed significant bacterial growth, with Enterobacteriaceae comprising 130 isolates (86.7%). Escherichia coli was the most frequently isolated species (n = 35 ESBL isolates, 70%), followed by Klebsiella pneumoniae (n = 12, 24%), Proteus mirabilis (n = 2, 4%), and Enterobacter cloacae (n = 1, 2%). Overall, 50 isolates (38.5%) were confirmed as ESBL producers. Resistance was highest against ampicillin (84.6%), ceftriaxone (55.4%), and cefotaxime (53.8%), whereas carbapenem resistance remained low (3.8%). Multidrug resistance (MDR) was observed in 60% of Enterobacteriaceae isolates. ESBL prevalence was higher in females (64%) and hospitalized patients (56%). Significant risk factors for ESBL infection included prior antibiotic use (p < 0.01), indwelling urinary catheters (p < 0.01), and recurrent UTIs (p = 0.02). ESBL-producing Enterobacteriaceae are highly prevalent among UTI patients, particularly in hospitalized individuals and those with prior antibiotic exposure or indwelling catheters. High rates of multidrug resistance emphasize the need for routine antimicrobial susceptibility testing, careful antibiotic stewardship, and stringent infection control measures to mitigate the spread of resistant uropathogens.